Improving The Ability of Mothers in Stimulation Toodler Development - Sri Endriyani; Eva Susanti (UrbanGreen, 2020)
One of the efforts to maintain and improve mental health in the community, especially children aged toodler, is to optimize the stimulation of growth and development of children aged toodler in order to achieve developmental tasks according to stages and ages. This study aims to see the increase in the ability of parents to stimulate growth and development of Todler-aged children.The design used in this study was